Melamine‐Doped Covalent Organic Framework Membranes for Enhanced Hydrogen Purification. Issue 22 (5th October 2021) - Zheng, Wei; Hou, Junjun; Liu, Cuijing; Liu, Pengchao; Li, Lianshan; Chen, Li; Tang, Zhiyong
Abstract: Covalent organic frameworks (COFs) are promising materials for membrane separation thanks to their adjustable topological structures and surface properties of nanopores. Herein, a melamine (Me)‐doped COF membrane was fabricated by chemically doping the melamine monomer into TpPa COF, which is formed by the condensation reaction between the 1, 3, 5‐triformylphloroglucinol (Tp) and p‐phenylenediamine (Pa) monomers via interfacial polymerization. The introduction of melamine monomer allows altering both the pore structure and pore surface of the TpPa COF membrane, leading to enhanced hydrogen purification performance. Specifically, the separation factor of H2 /CO2 gas mixture by using the melamine doped TpPa COF (TpPaMe COF) membrane reaches 12.7, with a hydrogen permeance of 727 GPU, in sharp contrast to the relatively low separation factor and gas permeance of 7.5 and 618 GPU of the undoped TpPa membrane. Besides, the TpPaMe COF membrane shows good running stability, with H2 /CO2 separation performance well surpasses the Robeson 2008 upper bound. Abstract : An effective molecular doping approach to fabricate composite covalent organic framework (COF) membranes with enhanced gas separation performance is reported.